Less common forms of diabetes in young population - Anna Tekielak; Ewa Otto-Buczkowska; Ewa Rusak (Pediatric Endocrinology, Diabetes and Metabolism)
Types diabetes other than type 1 are generally considered rare in children and adolescents. The incidence of type 2 diabetes has increased dramatically over the past decade in some ethnic groups. The increased incidence of this type of diabetes mellitus has corresponded tem-porally to unprecedented increases in body weight and obesity prevalence in adolescents in various ethnic populations. Early treatment of insulin resistance is important to prevent the development of diabetes. In therapy, lifestyle modification is essential for weight loss, and if this is not enough, pharmacotherapy is required. Maturity-onset diabetes of the young (MODY), another type of insulin-dependent diabetes, is characterised by early onset and autosomal dominant inheritance. MODY is mainly caused by β-cell defects, resulting in insufficient insulin secretion for a given blood glucose level. Unlike non-insulin-dependent diabetes in youth (NIDDM-Y), there is no significant increase in insulin resistance. The purpose of this article is to characterise and present types of diabetes other than type 1 found in the young population.